Eritrea - Eliminating a Harmful Traditional Practice - Wolff, Peter H. (World Bank, Washington, DC, 2012)
Female genital mutilation is wide-spread throughout many regions of Africa and elsewhere. It is usually perpetrated during early childhood and has serious consequences for the medical, gynecological, and obstetrical well-being of girls. These effects persist throughout the childbearing years and beyond. Less often recognized are the psychological suffering, humiliation social dignity, and self-concepts of the girls and women subjected to this traditional practice. The quickest solution for stopping the practice of female genital mutilation might appear to be to forbid the practice and to impose penalties on those who continued the practice. However, in view of the delicate relationship between the independence forces and the civilian population, it would have been politically inappropriate to impose such legal measures. Instead, the independent forces relied on the inherent intelligence and willingness of the Traditional Birth Attendants to modify their gynecological practices gradually, once they were given the necessary modern medical information. This approach also laid the groundwork for the continuing education of women by women after independence--an additional step towards assuring the equality of women.